The invasive red lionfish, Pterois volitans (Linnaeus 1758), in the southwestern Caribbean Sea (2009)
Here, we record the presence of the invasive Indo-Pacific lionfish (Pterois volitans) in Colombia based on six individuals collected in the Parque Nacional Natural Tayrona, Santa Marta (southern Caribbean), as well as two individuals observed in San Andres Island (western Caribbean) during May-July 2009. This is the first report of lionfish from South America.